IMMU-06. DELTA-24-RGD EXPRESSING POSITIVE IMMUNE MODULATORS SHOW ANTI-DIPG EFFECT AND INCREASE TUMOR IMMUNE INFILTRATION. (1st June 2021) - Laspidea, Virginia; Gupta, Sumit; Puigdelloses, Montserrat; Labiano, Sara; Ausejo-Mauleon, Iker; de la Nava, Daniel; Becher, Oren J; Gumin, Joy; Fueyo, Juan; Gomez-Manzano, Candelaria; Alonso, Marta M
Abstract: Diffuse Intrinsic Pontine Gliomas (DIPG) are aggressive pediatric brain tumors that arise in the pons of children, being the leading cause of pediatric death caused by cancer. We have previously demonstrated that Delta-24-RGD administration is safe and efficacious in DIPG preclinical models, indicating that it could be a good candidate as therapeutic approach for DIPG. However, our data underscore that there is still room to improve the anti-DIPG effect obtained with Delta-24-RGD. For that purpose, we have constructed three new virus by engineering Delta-24-RGD with different T cell activators: 4-1BBL (Delta-24-ACT), OX40-L (Delta-24-RGDOX) and GITRL (Delta-24-GREAT), to further increase the immune response generated by the viral effect. In vitro, the three virus were able to infect murine and human DIPG cell lines, produce oncolytic effect in a dose-dependent manner and express the corresponding functional ligand (4-1BBL, OX40L or GITRL) in the membrane of infected cells (almost 100% of cells expressing them at 10 MOIs). As expected, viral replication was optimal in human cell lines but semipermissive in murine cells. In vivo, the intratumoral administration of armed oncolytic viruses was safe and significantly increased survival of mice bearing orthotopic DIPG murine tumors, leading to long-term survivors. In addition, we analyzed the effect of the virus in the tumor microenvironment by flow cytometry and immunohistochemistry, which indicated that there was a significant increase of immune infiltration in brains of treated mice. Moreover, the immune infiltrated showed a functional active phenotype. Although deeper characterization is needed, these data show that the incorporation of a positive immune modulator into Delta-24-RGD could improve the oncolytic effect of the virus by boosting the immune response, while maintaining a safe profile in immunocompetent models offering a feasible option treatment for DIPG.